Penilaian Otentik Dalam Konteks Penilaian Karakter - Wilda Andriani; Rizki Sudrajat; Daniel Stefanus Marpaung; Ratna Sari Dewi (Journal of Creative Student Research, 2023)
In the learning process, not only subjects must be applied, but the development of student character is also important and emphasized. Education and character building are very important for everyone because they shape everyone's identity. Education and character building really need to be implemented from an early age so that it is better understood and accepted, and becomes an individual person from an early age. This is to ensure that students are trained to behave well at all times from a young age. Of course, there are many important challenges involved in developing student character. In addition, regular guidance and follow-up is needed to determine the character development of students. Authentic assessment is also needed to support the evaluation of student character, so that the results are more convincing and the original purpose of the process is achieved properly. Based on this explanation, the author tries to explain how authentic assessment should be carried out in the context of character assessment.